Increasing Paddy Productivity in Tidal Low Lands of South Sumatra through the Implementation of New Superior Varieties and Amator - Yeni Eliza Maryana; Agus Suprihatin; Budi Raharjo; Niluh Putu Sri Ratmini (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Efforts to increase the productivity of lowland paddy in tidal low land can be conducted through improving planting methods and the use of new superior varieties (NSV). This study aimed to find out the effect of using Amator on the cultivation of new high yielding varieties (NSV) in tidal paddy fields. This study used a Split Plot design, with the main plots namely planting equipment: using Amator and Sonor, and as subplots using NSV paddy: Hipa-18, Hipa-20, Hipa-21, and Inpari 22, with 3 replications. The results showed that the average productivity of NSV paddy using Amator was 5.2 t/ha, while that of Sonor reached 6.5 t/ha. Hybrid varieties (Hipa 18, Hipa 20, Hipa 21) grown using Amator produced taller paddy plants, more tillers and longer panicles than the inbred variety (Inpari 22) grown with Sonor. The productivity of the four NSV paddy tested gave a fairly high GDH (Grain Dry Harvest) yield of 5.6 – 6.2 t/ha.